1988
DOI: 10.1002/jor.1100060308
|View full text |Cite
|
Sign up to set email alerts
|

Strength reductions from metastatic cortical defects in long bones

Abstract: The purpose of this investigation was to measure the reduction in bone strength resulting from drill holes in diaphyseal bone and to compare this with finite element and theoretical predictions for stresses in a tubular structure. Fifty-two pairs of canine femora were tested to failure in four-point bending. One bone of each pair was used as the control; the other femora had holes of variable size drilled in the lateral cortex. At a ratio of drill hole diameter to bone diameter of 0.2, the bone retained only 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 20 publications
0
44
1
Order By: Relevance
“…Moreover, the callus strength in active locking plate group specimens was likely greater than the reported strength results, as failure occurred by spiral fracture through screw holes outside the callus zone. Extrapolating from a cadaveric study on the effects of screw holes on diaphyseal strength 35 , a 4.5-mm screw hole will reduce the strength of the ovine tibia by 15% to 30%, which would fully account for the observed strength loss in active locking plate group specimens compared with contralateral tibiae. In contrast, the finding that half of all standard locking plate group specimens recovered <10% of their native strength, and none recovered more than 43% of their native strength, provides further evidence that excessively stiff fixation suppresses healing.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, the callus strength in active locking plate group specimens was likely greater than the reported strength results, as failure occurred by spiral fracture through screw holes outside the callus zone. Extrapolating from a cadaveric study on the effects of screw holes on diaphyseal strength 35 , a 4.5-mm screw hole will reduce the strength of the ovine tibia by 15% to 30%, which would fully account for the observed strength loss in active locking plate group specimens compared with contralateral tibiae. In contrast, the finding that half of all standard locking plate group specimens recovered <10% of their native strength, and none recovered more than 43% of their native strength, provides further evidence that excessively stiff fixation suppresses healing.…”
Section: Discussionmentioning
confidence: 98%
“…In larger animal models the effect of the size of cortical holes on biomechanical properties has been determined. McBroom et al [20] determined the biomechanical properties with variable cortical hole sizes in canine femurs. They performed fourpoint bending and concluded that a ratio of drill hole diameter to bone diameter of 0.2 leads to a 38% strength reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have analyzed the effect of transcortical holes. 26,44,[53][54][55][56][57][58][59] We suspect that inclusion of a stress concentration factor would improve our strength estimates. However, the clinical setting was more closely replicated by not correcting for this.…”
Section: Discussionmentioning
confidence: 99%
“…Structural properties, such as bending and torsional strength, have been estimated using crosssectional information obtained from radiographs, absorptiometry (single and dual energy), and computed tomography (CT). 26,27,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] The weakness of radiograph-based estimates is that they require assumptions of cross-sectional shape and measurements of often indistinct inner cortical boundaries. Dual-energy X-ray absorptiometry (DXA), a convenient and economical method for accurately measuring bone mass and density, has been used to estimate strength.…”
Section: Introductionmentioning
confidence: 99%